The Effect of Project-Based Learning Model with Hybrid Mode on Higher Order Thinking Skills and Social Attitudes of Prospective Physics Teacher Students - Hikmawati*, Hikmawati; Taufik, Muhammad; 'Ardhuha, Jannatin; Muliadi, Irman; Rahayu, Satutik; Doyan, Aris; Faresta, Rangga Alif (Jurnal Pendidikan Sains Indonesia, 2025)
The project-based learning (PjBL) model with hybrid mode supports higher order thinking skills (HOTS) preparing students to become adaptive, creative, and competent educators in the 21st century. This study aims to analyze the effect of PjBL model with a hybrid mode on HOTS and social attitudes of prospective physics teacher students. This study was conducted on 5th semester students of the physics education study program, University of Mataram, who took the physics curriculum review course. The research design used was a quasi-experiment with a posttest only control group design. The study population included 75 students from class 5A, class 5B, and class 5C in the 2024/2025 academic year. The research subjects were divided into two groups, namely the experimental class (5A) and the control class (5C). The instruments used included a HOTS test and a social attitude questionnaire. Data analysis was performed using one-way Manova statistics. The results showed a significant difference in students' HOTS between the experimental class and the control class with an average HOTS of students in the experimental class of 81, higher than the control class which obtained an average score of 72. However, there was no significant difference in students' social attitudes between the two classes with an average score of social attitudes in the experimental class of 83 and in the control class of 82. This finding indicates that the PjBL model with a hybrid mode is effective in improving students' HOTS, but has little effect on the development of students' social attitudes.